Knowledge and Family Support with Personal Hygiene Independence in Children with Intellectual Disabilities - Monica Regina Caeli; Tuti Asrianti Utami; Sudibyo Supardi (Jurnal Keperawatan Profesional (KEPO), 2026)
Children with intellectual disabilities possess below-average intelligence, which impacts their growth and ability to perform personal hygiene independently. The family is the primary environment that shapes a child's independence. This study aimed to analyze the relationship between family knowledge and support and personal hygiene independence among children with intellectual disabilities in Bogor City. A quantitative cross-sectional design was used, involving 73 subjects through total sampling at State Special Schools in Bogor City between December 2024 and February 2025. Data were collected using validated questionnaires and analyzed using univariate distribution and the chi-square test (with Fisher's Exact Test as an alternative when assumptions were violated). The majority of parents had insufficient knowledge and the majority of children were in the dependent category. Among the four dimensions of family support examined, only emotional support showed a statistically meaningful association with the child's personal hygiene independence. It was concluded that, among the variables studied, emotional support from the family is the dominant factor associated with personal hygiene independence in children with intellectual disabilities. It is recommended that families strengthen emotional support, in the form of affection, encouragement, and consistent training at home, to foster personal hygiene independence in children with intellectual disabilities.